2015
DOI: 10.2139/ssrn.2623925
|View full text |Cite
|
Sign up to set email alerts
|

The Fallacy of Limited Financial Resources for Development in Tanzania: Evidence from Local Government Authorities Audit Reports

Abstract: Often times people are told by government officials that there are limited financial resources to finance different development projects/programmes and to provide assistance for self help. This view is also held by the academic world. This is usually taken as an absolute truth and usually as an excuse for the limited socio-economic development of the citizens and societies. While this may be true, we propose a problematisation of this by gathering and making sense of evidence from the annual audit reports for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…Due to that belief, some loan defaulters were not followed or harassed because they belonged to the ruling political party. These respondents' claims are in line with findings by National Audit Report of 2014 cited in Poncian (2015) which showed that 58 Local Govern Authorities did not recover WDF and YDF amounting Tanzania shillings 1, 389,192,866. The FGD findings were consistent with findings from Key Informants from the community development office who oversaw the fund/loan distribution who revealed that the biggest challenge was having many people in need but little money for disbursement. The KI commented as follows:…”
Section: Impact Informal Labour Market Conditions On Secondary Schoolsupporting
confidence: 87%
“…Due to that belief, some loan defaulters were not followed or harassed because they belonged to the ruling political party. These respondents' claims are in line with findings by National Audit Report of 2014 cited in Poncian (2015) which showed that 58 Local Govern Authorities did not recover WDF and YDF amounting Tanzania shillings 1, 389,192,866. The FGD findings were consistent with findings from Key Informants from the community development office who oversaw the fund/loan distribution who revealed that the biggest challenge was having many people in need but little money for disbursement. The KI commented as follows:…”
Section: Impact Informal Labour Market Conditions On Secondary Schoolsupporting
confidence: 87%
“…Several reports and studies have described the prevalence of money laundering predicate offenses such as the trade-in counterfeit goods (Confederation of Tanzania Industries, 2017), trafficking of persons (Kamazima et al , 2016) and misappropriations of funds and properties allocated to the central government, local governments, government entities and public parastatals (Killian, 2010; Poncian and Mpambije, 2015; Poncian, 2017) [9]. Definitely, law breakers generate and acquire illicit funds and non-financial assets from the above criminal activities and such funds are subsequently laundered in or outside Tanzania.…”
Section: Money Laundering Situation In Tanzaniamentioning
confidence: 99%
“…CHF Act of 2001 stipulates usage of CHF funds on issues like purchasing of medicine, hospital equipment, minor building repair, paying water and electricity bills, paying allowance to watchmen, etc. Having unspent amounts of money implies that some of the services and procurements that could be done for CHF to function properly were not done [59]. This, in turn, debilitates possible performance of CHF in the already poor performing districts.…”
Section: Twenty Years Of Chf Operation Under Decentralization System:mentioning
confidence: 99%